2018
DOI: 10.1007/978-3-319-98334-9_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating QBF Solvers: Quantifier Alternations Matter

Abstract: We present an experimental study of the effects of quantifier alternations on the evaluation of quantified Boolean formula (QBF) solvers. The number of quantifier alternations in a QBF in prenex conjunctive normal form (PCNF) is directly related to the theoretical hardness of the respective QBF satisfiability problem in the polynomial hierarchy. We show empirically that the performance of solvers based on different solving paradigms substantially varies depending on the numbers of alternations in PCNFs. In rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
(73 reference statements)
0
17
0
Order By: Relevance
“…In almost all cases, the solver that handles ψ ∀ needs more time than the solver that handles ψ ∃ . This may be founded on the observation that many QBFs have considerably more existential variables than universal variables [36], hence the instantiations added to ψ ∀ are much larger than the instantiations added to ψ ∃ .…”
Section: Methodsmentioning
confidence: 99%
“…In almost all cases, the solver that handles ψ ∀ needs more time than the solver that handles ψ ∃ . This may be founded on the observation that many QBFs have considerably more existential variables than universal variables [36], hence the instantiations added to ψ ∀ are much larger than the instantiations added to ψ ∃ .…”
Section: Methodsmentioning
confidence: 99%
“…Further, we considered the 402 PCNFs in their original form and preprocessed by Bloqqer and partitioned them into subsets containing PCNFs with at most two and with three or more quantifier alternations. Such partitioning is motivated by a related experimental study [30] where a large diversity of solver performance was observed on instance classes defined by alternations. Tables 2 and 3 show solver performance on these subsets without and with preprocessing, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Generally speaking, expansion/abstraction solvers tend to do better on instances with few alternations, whereas QCDCL solvers are at an advantage on instances with many alternations. Standard benchmark sets contain many instances with only a single alternation (Lonsing & Egly, 2018), presumably because many problems of interest can be encoded in such formulas. Figure 3 shows the number of solved prenex non-CNF instances broken down by the number of quantifier alternations.…”
Section: Decision Heuristic Restart Strategy and Constraint Deletion Policymentioning
confidence: 99%